Features of Rehabilitation Therapy for Patients with Symptomatic Epilepsy (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
At present, comprehensive rehabilitation and social integration of children with disabilities is one of the priorities of the state social policy of the Republic of Uzbekistan. However, cerebral palsy is also accompanied by the so-called optional symptoms of damage to the central nervous system, which, although not included in the mandatory pathological symptom complex, significantly complicate treatment and worsen the rehabilitation prognosis of the disease.